HBR's 10 must reads on diversity (HBR's 10 must reads (Series), 2019)
In today's competitive hiring market, you can't risk excluding or alienating talented employees--regardless of their gender, race, class, or physical ability. Bias can seep into the deepest corners of your workplace and hinder both the success of the people who hold marginalized identities and your organization as a whole. What sort of hiring procedures, employee development programs, and personnel policies can eradicate the biases that cause discrimination? One-day mandatory diversity seminars aren't enough. If you read nothing else on achieving diversity, read these 10 articles by experts in the field. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you challenge your company's thinking--and infrastructure--on creating a culture that seeks and celebrates differences. This book will inspire you to: Understand and eradicate bias Break down unspoken barriers Attract, retain, and engage talent that represents many diverse identities Question how you think about and promote equality Establish company policies and practices that are inclusive Develop a culture that offers every employee equal access to opportunities for growth--